2014
DOI: 10.1007/s12195-014-0340-0
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Multi-scale Vascular Network System Within 3D Hydrogel Using 3D Bio-printing Technology

Abstract: Although 3D bio-printing technology has great potential in creating complex tissues with multiple cell types and matrices, maintaining the viability of thick tissue construct for tissue growth and maturation after the printing is challenging due to lack of vascular perfusion. Perfused capillary network can be a solution for this issue; however, construction of a complete capillary network at single cell level using the existing technology is nearly impossible due to limitations in time and spatial resolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
243
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(259 citation statements)
references
References 56 publications
(90 reference statements)
1
243
1
2
Order By: Relevance
“…[53] In these multicellular aggregates, the need for supporting gels or matrices is eliminated, the adverse effects 3D culture approach for generating a laminated cerebral cortex like structure from pluripotent stem cells. [57,58] Microfabrication Neuroprogenitor cells Microfluidic culture platform containing a relief pattern of soma and axonal compartments connected by microgrooves to direct, isolate, lesion, and biochemically analyze CNS axons [67,68] 3D bioprinting Primary human cortical neurons Discrete layers of primary neutrons in a RGD peptide-modified gellan gum [118][119][120] Intestine (Gut) Self-assembled Stem cells Identified intestinal stem cells and differentiated cells in vitro [59,60] Microfabrication Human epithelial cells Mimic contractility by using mechanochemical actuator [11,19,27,72] Liver Self-assembled Human stem cells 3D culture of self-renewing human liver tissue [61,62] Microfabrication Hepatocytes and fibroblasts Microengineered hepatic microtissues containing hepatocytes and fibroblasts [73][74][75][76][77] 3D bioprinting HepG2 and HUVEC Multilayered organ tissue model [96,[155][156][157] Vessel Microfabrication Rat brain endothelial cells 3D culture in microfluidic device [63][64][65][66] 3D bioprinting HUVECs and HUVSMCs Scaffold-less vessel formation using spheroid fusion [84][85][86][87][88][89][90][91]…”
Section: Engineering Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[53] In these multicellular aggregates, the need for supporting gels or matrices is eliminated, the adverse effects 3D culture approach for generating a laminated cerebral cortex like structure from pluripotent stem cells. [57,58] Microfabrication Neuroprogenitor cells Microfluidic culture platform containing a relief pattern of soma and axonal compartments connected by microgrooves to direct, isolate, lesion, and biochemically analyze CNS axons [67,68] 3D bioprinting Primary human cortical neurons Discrete layers of primary neutrons in a RGD peptide-modified gellan gum [118][119][120] Intestine (Gut) Self-assembled Stem cells Identified intestinal stem cells and differentiated cells in vitro [59,60] Microfabrication Human epithelial cells Mimic contractility by using mechanochemical actuator [11,19,27,72] Liver Self-assembled Human stem cells 3D culture of self-renewing human liver tissue [61,62] Microfabrication Hepatocytes and fibroblasts Microengineered hepatic microtissues containing hepatocytes and fibroblasts [73][74][75][76][77] 3D bioprinting HepG2 and HUVEC Multilayered organ tissue model [96,[155][156][157] Vessel Microfabrication Rat brain endothelial cells 3D culture in microfluidic device [63][64][65][66] 3D bioprinting HUVECs and HUVSMCs Scaffold-less vessel formation using spheroid fusion [84][85][86][87][88][89][90][91]…”
Section: Engineering Technologiesmentioning
confidence: 99%
“…[88] These vessel generation methods promoted the development of physiologically relevant vascularization and perfusion models. [89,90] Using biological laser printing (BioLP), branch/stem structures of HUVEC and human umbilical vein smooth muscle cells (HUVSMC) were fabricated. [91] The printed structure mimicked vascular networks in tissue and allowed angiogenesis, i.e., the sprouting of new, finer vessels away from the stem Adv.…”
Section: Bioprinted Vesselsmentioning
confidence: 99%
“…Another use for fugitive inks is the creation of perfusable channels within other structures, these materials have the mechanical stability to maintain shape while the entire tissue is printed, but can be washed away at a later time, leaving perfusable channels in whatever configuration is needed [4,7,8]. The standard process creates a regular geometric network structure first via bioprinting before cast moulding the desired bulk material around it -epoxy resin for microfluidic devices or cells suspended within a hydrogel -finally the sacrificial structure is removed and the resulting perfusable channels are lined with endothelial cells [4,9].…”
Section: Internal Channel Creation Via Fugitive Inksmentioning
confidence: 99%
“…This helps to keep cells alive all throughout the construct, and more importantly, to perfuse it with growth factors that differentiate the printed Mesenchymal Stem Cells (MSCs) toward the osteogenic lineage. Lee et al [8] showed that by not only lining the channels with endothelial cells, but also incorporating endothelial cells within the printed construct, micro-vascularisation is created between the larger channels.…”
Section: Internal Channel Creation Via Fugitive Inksmentioning
confidence: 99%
“…The known 3D printed vascular models are presented with diameters of 500-1500 µm, but show a cell composition comparable to the much smaller capillaries 1,2 . To mimic vascular channels ranging from the size of arterioles and venules to arteries and veins three cell types are included within the three different walls of a channel.…”
Section: S03-05mentioning
confidence: 99%